2018
DOI: 10.4236/jhrss.2018.61028
|View full text |Cite
|
Sign up to set email alerts
|

Family-Friendly Human Resource Practice, Organizational Commitment, and Job Performance among Employees: The Mediating Role of Workplace Spirituality

Abstract: The aim of this article is to examine the effect of family-friendly human resource practice on employees' organizational commitment and job performance, and the role of workplace spirituality fit within the prior relationship. To this end, this research collects 347 samples data, and conducts a hierarchical regression analysis. The results show that family-friendly human resource practice has a significant positive effect on the organizational commitment and job performance of employees, whilst workplace spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Using the meta-analysis completed by other researchers (among others, Meyer et al , 2002; Darwish, 2003; Choi et al , 2015; Kabins et al , 2016), their results revealed a positive relationship with the affective dimension, while the other dimensions studied presented low levels of relationship. On the other hand, recent studies (among others, Takamatsu and Yamaguchi, 2018; Ke and Deng, 2018; Shahid and Zain, 2018; Mackay, 2018) confirm the one-dimensionality of this construct.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Using the meta-analysis completed by other researchers (among others, Meyer et al , 2002; Darwish, 2003; Choi et al , 2015; Kabins et al , 2016), their results revealed a positive relationship with the affective dimension, while the other dimensions studied presented low levels of relationship. On the other hand, recent studies (among others, Takamatsu and Yamaguchi, 2018; Ke and Deng, 2018; Shahid and Zain, 2018; Mackay, 2018) confirm the one-dimensionality of this construct.…”
Section: Discussionmentioning
confidence: 79%
“…Some important aspects and characteristics considered in this model should be noted: (1) a strong belief and acceptance of the aims and values of the organization; (2) a will to exercise considerable effort in the name of the organization; and (3) a defined wish to continue being a member of the organization so that affective adherence is emphasized (Mowday et al , 1979). As we have said before, other empirical studies use the one-dimensional model of organizational commitment as their reference (among others, Darwish, 2003; Ke and Deng, 2018; Takamatsu and Yamaguchi, 2018; Shahid and Zain, 2018) because it has suitable characteristics that are applicable in the business reality of economic globalization. From this point of view, the commitment would only really have an aspect related to the emotional and affective attachment to the organization someone works in.…”
Section: Literature Reviewmentioning
confidence: 99%
“…49/2018 is considered to cover the possibility of honorary teachers becoming permanent ASN teachers. Tabouli, Habtoor, & Disomimba (2016); Sapitri (2016); Jianglin & Xiuting (2018) indirectly show how organizational commitment to issued policies has an influence on employee performance.…”
Section: Government Policy Towards Work Stressmentioning
confidence: 99%
“…Based on the recent past studies (Ahmad & Omar, 2015;Ke & Deng, 2018;Ghani, Abdullah & Allah, 2018), there are an increasing attention from the researchers to examine the workplace spirituality in the organization. This research study seeked to study the influences of workplace spirituality (Allen & Meyer , 2000) on organizational commitments among university members in Malaysia.…”
Section: R E S E a R C H H I G H L I G H T Smentioning
confidence: 99%